Computational Quantification of the Physicochemical Effects of Heme Distortion: Redox Control in the Reaction Center Cytochrome Subunit of Blastochloris viridis. - MACGOWAN, STUART ALEXANDER; SENGE, MATHIAS (My University, 2013)
A facile, experimentally calibrated computational procedure is described that affords the relative ordering of heme cofactor reduction potentials with respect to intrinsic shifts brought about by apoprotein induced heme-macrocycle distortion. The method utilizes heme-Fe partial atomic charges and is useful with the computationally inexpensive B3LYP/3-21g method calculated for simplified heme models extracted from the Protein Data Bank incorporating only the effects of varying macrocycle conformations and thereby delineating their physicochemical effects. The procedure was successfully calibrated using the atomic coordinates and published mid-point potentials from the heme cofactors in wild-type and a series of heme-NO and ?O2 binding domain mutants and thus confirmed the sole conformational modulation of the redox potentials in these complexes. This technique was also applied to the reaction center tetraheme cytochrome subunit of Blastochloris viridis to build upon previous work elucidating the role that conformational control plays in photosynthetic systems and it was found that this effect may account for up to 70% (54mv) of the observed differences in the reduction potentials of the four hemes. We validate the approach using larger basis sets up to and including the triple-?, doubly polarized and augmented 6-311+g** basis and discuss the specific conformational origins of the effect.
PUBLISHED
Keywords: emeproteins; H-NOx; cytochromes; photosynthesis; reduction potential; crystal structures; DFT; structure-function correlation